How endogeneity problems are addressed in analyzing the relationship between diversity in top management teams and company financial performance—a systematic literature review - Tubik, Daniel; Herberger, Tim Alexander (Management Review Quarterly, 2024)
Endogeneity is a primary concern for empirical research that examines the relationship between firm leadership and company performance. This is especially true for demographic heterogeneity in boardrooms and top management teams, where reverse causalities are prevalent. Based on a systematic literature review, we contribute to the current state of empirical literature by highlighting the effects of mitigating endogeneity methodically, showing how studies differ in various types of demographic heterogeneity variables and endogeneity checks, and how all these influence performance outcomes in research. We thus offer a new perspective on the numerous empirical findings already available. Our findings show that most studies acknowledge and check for endogeneity concerns but do so by employing different methodical approaches. We further show that the utilization of various techniques affects the variability in study outcomes regarding relationship directions. Papers employing more sophisticated methods (e.g., System GMM) have a higher share of positive significant findings than our overall sample. Still, the general trend that an overwhelming share of papers finds at least some significant positive relationship between leadership demographic heterogeneity and financial performance holds firm all the techniques employed. We consider research created from 1990 to 2024 for our sample of 163 publications.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Diversity; Endogeneity; Financial performance; GMM; Systematic literature review; Top management teams